Perspective relationnelle du développement féminin - Spain, Armelle; Hamel, Sylvie (Canadian Journal of Counselling and Psychotherapy, 1996)
While considering self-development as a gradual separation from significant others, the currenttheoretical conceptualizations of adult psychological development call into question an evolutionthat would be realized through relationships. Nonetheless, recent research on women'sidentity shows that their sense of self is formed within the context of their interactions withothers. Thus, the relational component of women's development is put into focus. Threesources of this field of psychology are briefly presented and discussed in this article: the works ofJosselson, Gilligan and the Wellesley College's Stone Center. The relational perspective ondevelopment suggests reconsidering theories and practices in psychology and consequently in career counselling.